2022
DOI: 10.3389/fphar.2022.860383
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhiza Bunge (Danshen) and Bioactive Compound Tanshinone IIA Alleviates Cisplatin-Induced Acute Kidney Injury Through Regulating PXR/NF-κB Signaling

Abstract: Objective: The present study aims to provide evidence on the potential protective role of Salvia miltiorrhiza Bunge (Danshen) and its bioactive compound Tanshinone IIA (TanIIA) in AKI and to reveal the specific regulatory function of PXR/NF-κB signaling in AKI-induced renal inflammation.Methods: A network pharmacological analysis was used to study target genes and regulatory networks in the treatment of Salvia miltiorrhiza on AKI. Further experiments with in vivo AKI mouse model and in vitro studies were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Sustained-release preparations can markedly prolong the in vivo coexistence of tanshinone IIA, tanshinol, protocatechuic aldehyde, and salvianolic acid B in Danshen compared to the commercial Danshen capsules to enhance their overall effects [ 20 ]. Tanshinone IIA isolated from Danshen can alleviate cisplatin-induced acute kidney injury through the regulation of PXR/NF-κB signaling [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sustained-release preparations can markedly prolong the in vivo coexistence of tanshinone IIA, tanshinol, protocatechuic aldehyde, and salvianolic acid B in Danshen compared to the commercial Danshen capsules to enhance their overall effects [ 20 ]. Tanshinone IIA isolated from Danshen can alleviate cisplatin-induced acute kidney injury through the regulation of PXR/NF-κB signaling [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since traditional formulae in traditional Korean medicine are used in combination with various medicinal substances, network pharmacology from a holistic perspective plays an important role in understanding the effects and mechanisms of herbal medicines. For example, using network pharmacological analysis, Zhou and Wu showed that the mitogen-activated protein kinase pathway is a potential pharmacological pathway of Eucommiae cortex against osteoporosis [ 3 ], and Dou et al reported the protective effect of tanshinone II in Salvia miltiorrhiza Bunge in an acute kidney injury model through pregnane X receptor activation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%